2020
DOI: 10.1287/orsc.2019.1284
|View full text |Cite
|
Sign up to set email alerts
|

Practice Implementation Within a Multidivisional Firm: The Role of Institutional Pressures and Value Consistency

Abstract: This paper proposes a model to predict when the subunits of a multidivisional firm implement a practice adopted by the firm more or less extensively, focusing on the intraorganizational environment. Drawing on institutional arguments, I propose that a subunit’s extent of practice implementation is a combined result of coercive pressures from its headquarters, imitation of its peer units, and its own perception of the practice’s legitimacy. More specifically, I argue that a subunit will implement new practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 80 publications
1
26
0
Order By: Relevance
“…Theoretically, scholars have utilized a variety of lenses to understand the implementation of practices in MNCs. Important in this regard are: institutional perspectives which have, in particular, surfaced issues related to the gaining and maintaining of legitimacy (Jacqueminet, 2020; Kostova & Zaheer, 1999) and the dialectic surrounding the desire to standardize or localize HRM practices in MNC units operating across multiple contexts (Ferner, Belanjer, Tregaskis, Morley, & Quintanilla, 2013; Parry, Dickmann, & Morley, 2008); process perspectives, increasingly calling attention to the complexity surrounding implementation (Van Mierlo et al, 2018); and more recently paradox perspectives which underscore some of the contradictions inherent in different organizational settings and the efforts actors engage in to navigate them (Keegan, Bitterling, Sylva, & Hoeksema, 2018; Nadiv & Kuna, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, scholars have utilized a variety of lenses to understand the implementation of practices in MNCs. Important in this regard are: institutional perspectives which have, in particular, surfaced issues related to the gaining and maintaining of legitimacy (Jacqueminet, 2020; Kostova & Zaheer, 1999) and the dialectic surrounding the desire to standardize or localize HRM practices in MNC units operating across multiple contexts (Ferner, Belanjer, Tregaskis, Morley, & Quintanilla, 2013; Parry, Dickmann, & Morley, 2008); process perspectives, increasingly calling attention to the complexity surrounding implementation (Van Mierlo et al, 2018); and more recently paradox perspectives which underscore some of the contradictions inherent in different organizational settings and the efforts actors engage in to navigate them (Keegan, Bitterling, Sylva, & Hoeksema, 2018; Nadiv & Kuna, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to further aid meaning, we curated insights from on‐going practice observations made during the delivery of a succession of training and development interventions led by the first author, and from a range of assembled documents and artifacts relating to the HiPo programs designed and implemented by these MNCs. We adopt an intra‐unit perspective in the sense that we give consideration to some of the tensions that arise between actors who mandate and design the practice and those who are delegated to implement it (Jacqueminet, 2020). Overall, our study casts light on the various tensions that arise in the context of the implementation of HiPo programs over time and the ways in which salient proximal actors respond to attendant paradoxes as they unfold.…”
Section: Introductionmentioning
confidence: 99%
“…As such organizational hypocrisy is categorized as an organizational climatic factor in this study. Organizational hypocrisy is described as disjuncture or "decoupling" of the stated values, plans, and operational practices within organizations (Argyris & Schon, 1974;Bromley & Powell, 2012;Brunsson, 1993;Fernando & Gross, 2006;Huzzard & Östergren, 2002;Jacqueminet, 2020;2000;Meyer & Rowan, 1977;Posner & Kouzes, 1993). Furthermore, Brunsson (1989) postulates that inconsistencies in the outputs or products reflect inconsistencies in the environment.…”
Section: Effect Of Organizational Hypocrisy On Abusive Supervisionmentioning
confidence: 99%
“…In addition, it has been found that ethical climate effects behaviours of employees and unethical practices by the organizations may lead the employees to harbour turnover intentions (Mayer, Kuenzi, & Greenbaum, 2010;Mulki, Jaramillo, & Locander, 2008;Simha & Cullen, 2012;Yurtkoru, Ensari, & ErdilekKarabay, 2018). It has been observed that having values and consistent adherence to these values play a key role in the interpretation and implementation of practices (Jacqueminet, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several recent individual‐level studies reject the assumption that managers mechanically implement practices that are deemed to be effective or legitimate. In this view, a few authors maintain that practice adoption is not the result of legitimacy and efficacy factors in their own right but rather of people's evaluations of these factors (e.g., Bendoly & Cotteleer, 2008; Braunscheidel et al, 2011; Jacqueminet, 2020; Rogers et al, 2007). These studies suggest that managers, through complex cognitive processes, base their decisions and actions on their beliefs regarding the practice and the context (e.g., Croson et al, 2013; Eggers & Kaplan, 2013; Helfat & Peteraf, 2015; Kennedy & Fiss, 2009; Nadkarni & Barr, 2008).…”
Section: Introductionmentioning
confidence: 99%